2005
DOI: 10.4049/jimmunol.174.5.2746
|View full text |Cite
|
Sign up to set email alerts
|

Different Diabetogenic Potential of Autoaggressive CD8+ Clones Associated with IFN-γ-Inducible Protein 10 (CXC Chemokine Ligand 10) Production but Not Cytokine Expression, Cytolytic Activity, or Homing Characteristics

Abstract: Type 1 diabetes mellitus is an autoimmune disease characterized by T cell-mediated destruction of the insulin-producing β cells in the islets of Langerhans. From studies in animal models, CD8+ T cells recognizing autoantigens such as islet-specific glucose-6-phosphatase catalytic subunit-related protein, insulin, or glutamic acid decarboxylase (GAD) are believed to play important roles in both the early and late phases of β cell destruction. In this study, we investigated the factors governing the diabetogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 90 publications
(150 reference statements)
1
23
0
Order By: Relevance
“…Expression of CXCL10 within the pancreas has been linked to the recruitment of lymphocytes into the pancreas by a diabetogenic CD8 T cell clone, while expression within the PLN appears to retain autoreactive T cells and prevent pancreatic infiltration (30,33). Raised CXCL10 levels have been demonstrated after infection of mice with a number of pancreas-tropic viruses capable of triggering T1D in a mouse model, while neutralization of CXCL10 prevented T1D in this model (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of CXCL10 within the pancreas has been linked to the recruitment of lymphocytes into the pancreas by a diabetogenic CD8 T cell clone, while expression within the PLN appears to retain autoreactive T cells and prevent pancreatic infiltration (30,33). Raised CXCL10 levels have been demonstrated after infection of mice with a number of pancreas-tropic viruses capable of triggering T1D in a mouse model, while neutralization of CXCL10 prevented T1D in this model (34).…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of chemokines has been shown to control autoreactive T cell migration in the initiation and prevention of T1D (28,30,33). Prevention of T1D in NOD mice exposed to the NKT cell ligand ␣-galactosylceramide has been linked to alterations in chemokine expression patterns and the preferential retention of transferred autoreactive CD8 ϩ T cells in the PLN (44).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ejrnaes et al found that the diabetogenic potential of Tc1 clones is associated with IP-10 (CXCL10) production but not with cytokine expression, cytolytic activity, or homing characteristics. The IP-10-expressing Tc1 clone led to destructive insulitis characterized by the presence of more T cells and particularly macrophages, suggesting that CD8 ϩ T cells can induce diabetes by recruiting other immune cell types to the site of inflammation (48). We found similar low levels of IP-10 in OT-I cultures treated with TGF-␤1 plus IL-6 or IL-23, suggesting that IP-10 does not play a role in diabetogenicity of these cells (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of NP396-and GP33-specific NOD T-cell clones. The generation and maintenance of LCMV-specific T-cell clones in long-term cultures have been previously described (25,26). In brief, the NP396-specific NOD T-cell clone 9-A-8 and the GP33-specific NOD T-cell clone 13-G-8 were isolated from LCMV-infected NOD recipients and stimulated frequently with irradiated NP396 or GP33 peptide-loaded syngeneic macrophages, respectively, and recombinant human IL-2 (20 units/ml).…”
Section: Methodsmentioning
confidence: 99%